Analysis of Factors That Influence The Level of Patient Satisfaction in Online Registration at The Ngancar Health Center, Kediri District - Evi Sita Dewi; Sentot Imam Suprapto (Universitas STRADA Indonesia, 2024)
Patient assessments of health worker services come from the patient's experience. The patient experience aspect can be interpreted as a treatment or action from a nurse that is or has been experienced, felt and endured by someone who uses health services. The aim of this research is to analyze the influence of service quality and perception on the level of patient satisfaction in registering online at the Ngancar Community Health Center, Kediri Regency. The design of this research is quantitative observational research with a cross sectional approach with the focus of the research directed at analyzing the influence of service quality and perceptions on the level of patient satisfaction in carrying out online registration at the Ngancar Community Health Center, Kediri Regency with a population of 72 respondents and a sample of 53 respondents taken using techniques. Accidental Sampling. The findings showed that the majority of respondents had good service quality, 27 respondents (50.9%). Most respondents had a good category perception as many as 28 respondents (52.8%). Most respondents had satisfaction in the satisfied category, 30 respondents (56.6%). The results of research using the Logistic Regression Test show that with a p-value < 0.05, H1 is accepted so it can be concluded that simultaneously there is an influence of service quality and perception on the level of patient satisfaction in registering online at the Ngancar Community Health Center, Kediri Regency. It is hoped that respondents can provide input and constructive criticism so that the online registration service provided can be as expected.